Customer-Perceived Insecurity of Online Shopping Environment - Matic, Matea; Vojvodic, Katija (International Review of Management and Marketing, 2013)
Customer-perceived insecurity of online shopping environment has become one of the major obstacles to the growth of electronic commerce. The main purpose of this study was to examine the influence of insecurity of Internet usage towards online purchase decision as well as consumers’ attitudes and intentions towards online purchasing. The data was collected through survey questionnaire using the purposive sample of 253 Croatian students from the University of Dubrovnik. Research results indicate a significant relationship between the insecurity of Internet usage and online purchase decision. Additionally, a significant relationship was found between the insecurity of Internet usage and consumers’ attitudes and intentions towards online purchasing. The overall analysis reveals that consumers have positive attitudes and intentions towards online purchasing whilst insecurity towards online purchasing lowers when online purchases are made more frequently. Keywords: insecurity of Internet usage; online purchase decision; online purchase intention JEL Classifications: D12; L81